2007
DOI: 10.1038/sj.cdd.4402221
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular K+ inhibits apoptosis by suppressing the Apaf-1 apoptosome formation and subsequent downstream pathways but not cytochrome c release

Abstract: Cellular ionic homeostasis, fundamentally K þ homeostasis, has been implicated as a critical regulator of apoptosis. The intracellular K þ efflux on apoptotic insult and suppression of apoptosis by high concentration of extracellular K þ or after inhibition of this efflux by K þ channel blockers have established the crucial role of K þ in turning on the apoptotic machinery. Several contrasting observations have reported the antiapoptotic effect of intracellular K þ concentration to be the result of inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 40 publications
4
50
0
Order By: Relevance
“…In vitro experiments show that the K + threshold for inflammasome inhibition is in the 70 mM range (Petrilli et al, 2007). This seems to be a common feature of inflammatory and apoptotic caspases (Karki et al, 2007;Arlehamn et al, 2010). The trigger role of K + depletion in caspase-1 activation was known long before the inflammasome was discovered thanks to the pioneering experiments of Gabel and co-workers who showed that the K + selective ionophore nigericin, but not the Na + selective ionophore monensin, Fig.…”
Section: Mechanism Of Activation Of the Inflammasomementioning
confidence: 99%
“…In vitro experiments show that the K + threshold for inflammasome inhibition is in the 70 mM range (Petrilli et al, 2007). This seems to be a common feature of inflammatory and apoptotic caspases (Karki et al, 2007;Arlehamn et al, 2010). The trigger role of K + depletion in caspase-1 activation was known long before the inflammasome was discovered thanks to the pioneering experiments of Gabel and co-workers who showed that the K + selective ionophore nigericin, but not the Na + selective ionophore monensin, Fig.…”
Section: Mechanism Of Activation Of the Inflammasomementioning
confidence: 99%
“…These proteins facilitate nucleotide exchange on Apaf-1, which is necessary for full apoptosome formation and subsequent caspase-9 activation. Interestingly, levels of other (nonprotein) cellular components, such nucleotides and ions, also appear to play critical roles in regulating certain steps in the activation of caspases and the apoptotic pathway (Cain et al 2001;Chandra et al 2006;Bao et al 2007;Karki et al 2007;Mei et al 2010). Because there have been a variety of recent reviews on the proteins that regulate caspases indirectly, these circumstances are not covered here (Schafer and Kornbluth 2006;Fadeel et al 2008;Krumschnabel et al 2009).…”
Section: Protein/protein Interactionsmentioning
confidence: 99%
“…However, the exact mechanism by which the reduction in GSH i modulates the activation of the execution phase of apoptosis is still imprecise. A necessary role of K ϩ loss for the activation of execution caspases and apoptosome formation has also been demonstrated (5,60,61), whereas Cl Ϫ loss does not seem to play an important role in this phenomenon (62). Thus, we analyzed if the modulation of the execution phase of apoptosis by GSH transport was linked to the regulation of K ϩ loss.…”
Section: Gsh Regulates the Execution Phase Of Apoptosis By The Modulamentioning
confidence: 99%